The technology innovation paradox in Asia’s leading innovative economies: the importance of renewable energy and green financing - Abdul Rehman; Hengyun Ma; Muhammad Irshad Ahmad; Zakia Batool; Brayan Tillaguango; Judith Oláh (Technological and Economic Development of Economy)
The present study investigates the influence of green energy, technological innovation, financial development, natural resources, trade, and economic growth on environmental quality in four technologically innovative economies in Asia using data from 1990 to 2021. By adopting a holistic approach, it addresses gaps in the literature that often focus on isolated factors or regions. The findings provide actionable insights for policymakers to reconcile economic growth with ecological sustainability, offering a blueprint for sustainable development in Asia’s technological hubs. The Panel ARDL approach is used to evaluate the impacts in both the long and short term. Furthermore, we performed robustness tests using panel least squares, panel FMOLS, and panel DOLS techniques. The study’s findings indicate that technological innovation, financial development, and trade all have a long-term positive impact on environmental quality in Asia’s technologically innovative economies. However, green energy, natural resources, and economic progress had a negative impact on CO2 emissions. The findings from panel least squares, panel FMOLS, and DOLS also showed that technological innovation, financial development, and trade enhance the environmental quality. This investigation aims to assist policymakers in creating comprehensive plan that promotes environmental sustainability via technological improvements and renewable energy sources, with an emphasis on economic growth.